Inclusive process in physical education classes: a study on sociometric test - doi: 10.4025/reveducfis.v21i3.7764 - Alves, Maria Luíza Tanure (2010)
Sociometric test is a toll which analyses social structures in response of choices and rejections within a group. Its utilization allows categorization of subjects according to social relationship built within a group and the analysis of his network. Our objective was to assess the functionality of sociometric test as an attractive evaluation tool of the inclusive process of children with disability in physical education classes. Subjects answered the sociometric test at the beginning and at the end of the school year. Subjects were then categorized according to sociometric indices achieved through choices made and rejections received within the group. This test allowed the structuring of the social network of this class, showing conflicting situations, students with relationship problems and how children with disability are seen by their peers. The results showed that student with disability had difficulty during school year in building social relationships. However, a limitation of this study is that the sociometric test can only assess the inclusive process from a social perspective and cannot evaluate issues like knowledge acquisition and participation in proposed activities.